Expiration dates : a novel [large type] - Serle, Rebecca (Thorndike Press large print top shelf., 2024)
"Daphne Bell believes the universe has a plan for her. Every time she meets a new man, she receives a slip of paper with his name and a number on it--the exact amount of time they will be together. She has been receiving the papers for over twenty years, always wondering when there might be one without an expiration. Finally, the night of a blind date at her favorite restaurant, there's only a name: Jake. But as Jake and Daphne's story unfolds, Daphne finds herself doubting the paper's prediction, and wrestling with what it means to be both committed and truthful. Because Daphne knows things Jake doesn't, information that--if he found out--would break his heart"--